Asesmen Perkembangan Seni Anak Usia Dini: Studi Praktik PKM di TK Negeri Pembina Telaga Jaya - Salsabila R. Solang; Naysila Napulo; Nunung Suryana Jamin; Annisa Fahmi Mannasai; Sri Indrawati Zakaria; Rapi Us. Djuko; Elva M. Sumirat; Nayla Faradilla; Adelia Putri Abas (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the practice of assessing early childhood art development through a community service program conducted at TK Negeri Pembina Telaga Jaya. The assessment was designed to capture children’s artistic development in a holistic manner, encompassing cognitive, fine motor, social-emotional, affective, and creative aspects. Using direct observation and structured assessment indicators, teachers were guided to evaluate not only the final artwork but also the artistic process, children’s engagement, emotional regulation, and creative expression. The findings indicate that art-based assessment provides rich and authentic data on children’s developmental progress, particularly in creativity, fine motor coordination, and emotional expression. The results also highlight the importance of teachers’ competence in conducting systematic and reflective assessments to support meaningful learning experiences. Moreover, art assessment was found to strengthen children’s motivation, confidence, and participation during learning activities. This study concludes that structured art assessment serves as an effective pedagogical tool that enhances the quality of early childhood education and supports holistic child development, while offering a practical assessment model that can be adapted by other early childhood education institutions.